INOVASI UBI UNGU MENJADI DONUT SEBAGAI KREATIVITAS PRODUK LOKAL DI KELURAHAN MANGUNSARI, KECAMATAN GUNUNGPATI, KOTA SEMARANG - Nurchayati, Nurchayati; Muchayatin, Muchayatin; Parju, Parju; Suyati, Sri; Setyobudi, Setyobudi; Sulistyani, Sulistyani; Aminah, Siti; Riyanto, Joko; Musprihadi, Ribut (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This community service program aims to empower the people of Mangunsari Village, Gunungpati District, Semarang City through purple sweet potato-based donut innovation. The main problem is the low added value of purple sweet potatoes, which are only sold raw, and limited knowledge of processed product diversification. The implementation method included training in donut making, packaging, branding, and marketing management for 25 participants. Results showed a significant increase in participant knowledge from 38% to 87%, with 92% of participants able to produce high-quality donuts. The optimal formulation using a 37.5% substitution of purple sweet potato puree resulted in an organoleptic acceptance level of 84-88%. Value-added analysis showed a 1,025% increase in economic value with a profit margin of 260%. The